Cloning, Expression And Purification Of Toxocara Canis Recombinant Antigens (Rtes-26, Rtes-32, Rtes-120) And Development Of Serodiagnostic Test For Toxocariasis - Mohamad, Suharni (2009)
In this study, recombinant T. canis DNA which encode for rTES-26, rTES-32 and rTES-120 were produced by cloning of open-reading frames (ORF) of the respective genes via reverse-transcriptase-PCR (RT-PCR) using mRNA extracted from a culture of T. canis second stage larvae into PCR2.1 TOPO vector. Dalam kajian ini, DNA rekombinan T. canis yang mengkodkan antigen rekombinan rTES-26, rTES-32 dan rTES-120 dihasilkan dengan mengklonkan kerangka bacaan terbuka gen masing-masing melalui kaedah “reverse-transcriptase-PCR” (RT-PCR) menggunakan mRNA yang diekstrak daripada kultur larva T. canis peringkat kedua ke dalam vektor PCR2.1 TOPO.